2003
DOI: 10.1038/sj.gt.3301919
|View full text |Cite
|
Sign up to set email alerts
|

A neovascularized organoid derived from retrovirally engineered bone marrow stroma leads to prolonged in vivo systemic delivery of erythropoietin in nonmyeloablated, immunocompetent mice

Abstract: Marrow stromal cells (MSCs) are postnatal progenitor cells that can be easily cultured ex vivo to large amounts. This feature is attractive for cell therapy applications where genetically engineered MSCs could serve as an autologous cellular vehicle for the delivery of therapeutic proteins. The usefulness of MSCs in transgenic cell therapy will rely upon their potential to engraft in nonmyeloablated, immunocompetent recipients. Further, the ability to deliver MSCs subcutaneously -as opposed to intravenous or i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
1
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 74 publications
2
46
1
1
Order By: Relevance
“…Plasma EPO levels were also found to be elevated for up to 7 weeks. 16 In comparison, subcutaneous transplantation of 10 7 EPO-engineered MSCs showed hematocrit levels that were increased to 70-80% and returned to normal after 40-50 days. 20,21 We i.p.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Plasma EPO levels were also found to be elevated for up to 7 weeks. 16 In comparison, subcutaneous transplantation of 10 7 EPO-engineered MSCs showed hematocrit levels that were increased to 70-80% and returned to normal after 40-50 days. 20,21 We i.p.…”
Section: Discussionmentioning
confidence: 92%
“…42 In conclusion, we find that nucleofection can be used to generate EPO-engineered MSCs, which secrete biologically active EPO in sufficient amounts to stimulate hematopoiesis in vivo. Future strategies aimed at the prevention of graft loss (for example, encapsulation of MSCs, exploitation of tissue tropism) 11,16,20 and inhibition of autoimmune responses are likely to extend the duration of action of this nonviral cell-based gene therapy where required.…”
Section: Nonviral Gene Transfer Into Murine Mscsmentioning
confidence: 99%
See 1 more Smart Citation
“…The s.c. delivery of MSCloaded scaffolds would provide an easily accessible implant that could be retrieved once the therapeutic effect is fulfilled or in the event of an unexpected adverse reaction. A seminal work by Eliopoulos et al 50 reported that erythropoietin (Epo)-secreting MSCs (MSC Epo ), when administered as 'free' cells by s.c or i.p. injection, led to a temporary hematocrit increase.…”
Section: Matrix-embedded Scdvs As Retrievable Sc Depotsmentioning
confidence: 99%
“…This differentiation plasticity makes MSCs the ultimate candidates for future utilization Therapeutic potential of bone marrow-derived mesenchymal stem cells producing pigment epithelium-derived factor in lung carcinoma in cell therapy and tissue regeneration (16,17). Furthermore, MSCs expressing transgenes maintained long-term expression (up to 6 months) in vivo because of their hypoimmunogenic properties and production of immunosuppressive molecules (18,19). The tumor microenvironment is known to provide a preferential niche for MSCs homing and survival.…”
Section: Introductionmentioning
confidence: 99%